2022
DOI: 10.1007/s10557-022-07328-w
|View full text |Cite
|
Sign up to set email alerts
|

A First-in-Human Study of AMG 986, a Novel Apelin Receptor Agonist, in Healthy Subjects and Heart Failure Patients

Abstract: Purpose AMG 986 is a novel apelin receptor (APJ) agonist that improves cardiac contractility in animal models without adversely impacting hemodynamics. This phase 1b study evaluated the safety/tolerability, pharmacokinetics, and pharmacodynamics of AMG 986 in healthy subjects and patients with heart failure (HF). Methods Healthy adults (Parts A/B) and HF patients (Part C) aged 18-85 years were randomized 3:1 to single-dose oral/IV AMG 986 or placebo (Part A); multiple-dose oral/IV AMG 986 or placebo (Part B); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…[Pyr 1 ] apelin infused systemically into volunteers ( Japp et al, 2008 ) has been shown to be safe and well tolerated, even at the highest concentration of 135 nmol/min for 120 min ( Nyimanu et al, 2019 ). A similar safety profile was also reported for the G-protein biassed agonist MM07 ( Brame et al, 2015 ) and the small molecule agonist ( Winkle et al, 2023 ) as well as for [Pyr 1 ] apelin in obesity ( Castan-Laurell et al, 2008 ) and patients with heart failure ( Japp et al, 2010 ). The results with agonists demonstrate apelin is limited to two principal actions in humans in health and disease: modest vasodilatation within the first hour of systemic infusion and a beneficial increase in cardiac output that is maintained for up to six hours in patients with heart failure ( Barnes et al, 2013 ).…”
Section: Discussionsupporting
confidence: 72%
“…[Pyr 1 ] apelin infused systemically into volunteers ( Japp et al, 2008 ) has been shown to be safe and well tolerated, even at the highest concentration of 135 nmol/min for 120 min ( Nyimanu et al, 2019 ). A similar safety profile was also reported for the G-protein biassed agonist MM07 ( Brame et al, 2015 ) and the small molecule agonist ( Winkle et al, 2023 ) as well as for [Pyr 1 ] apelin in obesity ( Castan-Laurell et al, 2008 ) and patients with heart failure ( Japp et al, 2010 ). The results with agonists demonstrate apelin is limited to two principal actions in humans in health and disease: modest vasodilatation within the first hour of systemic infusion and a beneficial increase in cardiac output that is maintained for up to six hours in patients with heart failure ( Barnes et al, 2013 ).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, acute administration of apelin in HF rapidly increased coronary blood flow, cardiac index, the maximum rate of rise in LV pressure and reduced peak and end-diastolic LV pressures, peripheral artery resistance, and mean arterial pressure [ 34 ]. At the same time, chronic administration of novel apelin receptor agonist AMG-986 did not demonstrate clinically meaningful pharmacodynamics effects in HFrEF [ 35 ]. However, there is a large volume of evidence that low levels of apelin may be a biomarker of adverse cardiac remodeling and untoward clinical course of HFrEF.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we hypothesized that dynamic changes of apelin levels controversially relate to cardiac hemodynamic performances in HFpEF and HFrEF and this interplay might be an attribute of altered metabolic homeostasis. The results of our study can be concisely explained if there is a protective effect of apelin in T2DM patients with known HF on cardiac structure and function is a result of uncoupling between the concentration of apelin and expression of its corresponding receptor (G protein-coupled receptor, APJ) on the surfaces of target cells including cardiac myocytes [ 35 ]. Indeed, apelin/APJ system alleviated mitochondrial dysfunction, which is a common phenomenon in T2DM-related and ischemia/hypoxia-induced cardiac myocyte injury [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two such long-acting agents that have shown promise in pre-clinical studies have undergone phase I trials. 179–181 Whilst data are as yet unpublished regarding BMS-986224, AMG 986 was shown to be safe and well tolerated in healthy humans and those with heart failure, although data were inconsistent regarding its clinical efficacy. 179 , 182 So far, neither agent has progressed to further studies.…”
Section: Therapeutic Targeting Of the Apelin Systemmentioning
confidence: 99%
“… 179–181 Whilst data are as yet unpublished regarding BMS-986224, AMG 986 was shown to be safe and well tolerated in healthy humans and those with heart failure, although data were inconsistent regarding its clinical efficacy. 179 , 182 So far, neither agent has progressed to further studies. The search for other small molecule agonists continues, and recently a small molecule known as compound 47 has been shown to be a potent and selective apelin receptor agonist.…”
Section: Therapeutic Targeting Of the Apelin Systemmentioning
confidence: 99%